2001
DOI: 10.1128/iai.69.5.2872-2877.2001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusFibronectin Binding Proteins Are Essential for Internalization by Osteoblasts but Do Not Account for Differences in Intracellular Levels of Bacteria

Abstract: Staphylococcus aureus is a major pathogen of bone that has been shown to be internalized by osteoblasts via a receptor-mediated pathway. Here we report that there are strain-dependent differences in the uptake of S. aureus by osteoblasts. An S. aureus septic arthritis isolate, LS-1, was internalized some 10-fold more than the laboratory strain 8325-4. Disruption of the genes for the fibronectin binding proteins in these two strains of S. aureus blocked their ability to be internalized by osteoblasts, thereby d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 32 publications
5
121
0
Order By: Relevance
“…Results with nonkeratinocyte cell types have shown that the process of internalization of S. aureus is depen- on May 11, 2018 by guest http://iai.asm.org/ dent on bacterial FnBPs and the host cell integrin ␣5␤1 (1,15,25,42). In the present study we investigated the role of S. aureus FnBPs and host cell integrins in bacterial internalization by keratinocytes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Results with nonkeratinocyte cell types have shown that the process of internalization of S. aureus is depen- on May 11, 2018 by guest http://iai.asm.org/ dent on bacterial FnBPs and the host cell integrin ␣5␤1 (1,15,25,42). In the present study we investigated the role of S. aureus FnBPs and host cell integrins in bacterial internalization by keratinocytes.…”
Section: Discussionmentioning
confidence: 87%
“…aureus is normally an extracellular pathogen; however, it can be internalized by a variety of nonphagocytic host cells in a fibronectin-binding protein (FnBP)-dependent manner. The host cells that have been studied to date include human umbilical vein endothelial cells (25), the human keratinocyte cell line HaCaT (28), corneal epithelial cells (20), osteoblasts (1), and epithelial 293 cells (a human embryonic kidney cell line) (42). In the previous studies the workers examined the interaction of host cells with S. aureus in vitro, but internalization of S. aureus by mammary gland epithelial cells has also been demonstrated in vivo (8).…”
mentioning
confidence: 99%
“…It also exhibits sequence similarity to putative fibronectin-binding proteins from B. subtilis, B. halodurans as well as the S. pneumoniae adherence and virulence protein A (42% identity). Streptococcal fibronectin-binding proteins (in particular pavA from S. pneumoniae) were shown to be essential for extra-cellular targeting and efficient cellular invasion (2,30,47,49,97,102,104).…”
Section: Resultsmentioning
confidence: 99%
“…The fibronectin binding assay was essentially a modification of that used by Ahmed et al (1). Costar 3590 96-well plates (Corning) were coated with 100 l of 0.02% sodium carbonate (pH 9.6) containing fibronectin (10 mg/ml; Sigma) overnight at 4°C and then blocked with 100 l of 2% bovine serum albumin solution for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%